Hubungan antara tingkat keaktifan dalam klub Prolanis dengan kualitas hidup pasien hipertensi di Puskesmas Bahu Kecamatan Malalayang Kota Manado - Kondoj, Srikandy Inri; Wariki, Windy Mariane Virenia; Siagian, Iyone Esra Tiurma (UNIVERSITAS SAM RATULANGI, 2025)
Background: Hypertension can reduce quality of life. The Prolanis Club program supports health stability through physical activity, education, and routine monitoring. Participant activity is thought to affect quality of life. Aim: To determine the relationship between activity levels in the Prolanis Club and the quality of life of hypertensive patients at the Bahu Community Health Center. Methods: A cross-sectional study of 44 hypertensive patients participating in Prolanis. Activity was assessed based on three-month attendance, and quality of life was measured using the EuroQol-5 Dimensions-5 Levels (EQ-5D-5L). Analysis was performed using the Chi-Square test (p < 0.05). Results: A total of 56.8% of respondents were classified as active. The majority (59.1%) had a good quality of life. There was a significant relationship between activity level and quality of life (p = 0.047; OR = 3.536; 95% CI = 1.001–12.485). Active participants were 3.5 times more likely to have a good quality of life than less active participants. Conclusion: Activity in the Prolanis Club is associated with the quality of life of hypertensive patients. More active patients are more likely to achieve a good quality of life.